2014
DOI: 10.3109/0886022x.2014.967615
|View full text |Cite
|
Sign up to set email alerts
|

Association of malnutrition-inflammation score, dialysis-malnutrition score and serum albumin with novel risk factors for cardiovascular diseases in hemodialysis patients

Abstract: Background: This study was designed to investigate the associations between malnutritioninflammation score (MIS), dialysis-malnutrition score (DMS) and serum albumin with novel risk factors for cardiovascular diseases (CVD) in hemodialysis (HD) patients. Methods: In this crosssectional study, 291 HD patients were randomly selected from among 2302 adult HD patients in Tehran HD centers. The MIS and DMS were determined during one of the dialysis sessions in these patients. In addition, 4 mL blood was obtained be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
(37 reference statements)
1
14
0
3
Order By: Relevance
“…By analyzing the nutritional status as a risk factor for cardiovascular disease in those patients, it was observed, through the regression model, that individuals with malnutrition had a higher prevalence of moderate and high cardiovascular risk. In Tehran, a study with 291 hemodialysis patients also found a significant association between malnutrition and increased risk of cardiovascular disease [27]. Moreover, Leavey et al [28] found a significant association between malnutrition and morbidity and mortality associated with cardiovascular disease in patients undergoing hemodialysis.…”
Section: Discussionmentioning
confidence: 97%
“…By analyzing the nutritional status as a risk factor for cardiovascular disease in those patients, it was observed, through the regression model, that individuals with malnutrition had a higher prevalence of moderate and high cardiovascular risk. In Tehran, a study with 291 hemodialysis patients also found a significant association between malnutrition and increased risk of cardiovascular disease [27]. Moreover, Leavey et al [28] found a significant association between malnutrition and morbidity and mortality associated with cardiovascular disease in patients undergoing hemodialysis.…”
Section: Discussionmentioning
confidence: 97%
“…Blood sample collection. Blood samples were collected according to the regular method (28). Fasting venous blood was extracted from 200 patients with uremia for detection of serum inflammatory factors.…”
Section: Methodsmentioning
confidence: 99%
“…Los sistemas de escalas nutricionales m SGA (subjective global assessment of nutritional status) es una escala simple y barata, con una alta aplicabilidad en la práctica clínica (18,28) . La escala PENS (protein-energy nutritional status) logra determinar una relación de la mortalidad con el valor sérico de la albúmina (23) .…”
Section: Estudios Complementariosunclassified